SUBJECTIVE WELL-BEING OF THE TENGGER TRIBE OF RANUPANI VILLAGE - Sari, Vina Budiarti Mustika; Wahjoedi, Wahjoedi; Pratikto, Heri; Wahyono, Hari (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
The main issue raised is how the subjective well-being of this community is influenced by unique cultural ties and traditional values, which are often overlooked in economic-based welfare measurements. This study aims to explore the subjective well-being of the Tengger Tribe community in Ranupani Village, East Java, which reflects the balance between material and non-material aspects. With a phenomenological approach and qualitative methods, this study uncovers the meaning of subjective well-being through in-depth interviews and observations of six key informants. The results show that subjective well-being in the Tengger Tribe community includes life satisfaction obtained from farming activities, sufficient income, availability of free time, and the application of traditional values such as Tri Hita Karana and the teachings of Bekti Marang Guru Papat. Spiritual ties, social solidarity, and harmony with nature also become the main pillars in creating well-being. The implication of this study is the need for local culture-based policies to support indigenous peoples' multidimensional well-being.